The Grammar of Interpersonal Meaning: A Content Analysis of a Selected Extract from Helon Habila’s the Chibock Girls: the Boko Haram Kidnappings and Islamist Militancy in Nigeria - KOUTCHADE, INNOCENT SOUROU; DATONDJI, COCOU ANDRÉ; YOKOSSI, Tchorkpa Daniel (My University, 2022)
Human language in its creative feature is mostly characterised by a constant alignment to the state of the mind and social relations impacted communications. This study has applied this linguistic pattern to an extract of Helon Habila’s The Chibock Girls through the grammar of interpersonal meaning within Halliday’s Systemic functional perspective. The analysis of mood choices (88.95% declaratives and 11.05% interrogatives) modality patterns (66.66% epistemic modality and 33.34% deontic modality) and adjunctive orientations (49.35% of circumstantial 35.89% of conjunctive, 6.41% of Mood 5.76% of continuity and 2.56% of Polarity adjuncts) has uncovered an overall tenor dimension of equal power, free talk and solidarity between the narrator, Ladi, the Chibock girls, Ruth and her husband.
Keywords: Interpersonal meaning; mood; modality; adjunct; tenor dimension